TOWARDS THEORIES OF DIGITAL WELL-BEING - Büchi, Moritz (AoIR Selected Papers of Internet Research, 2020)
How can we live a good life both thanks to and despite the constant use of digital media? The presented framework describes the nature of and connections between three relevant phenomena – digital media practices, harms/benefits, and well-being – and creates a blueprint for explanatory theories.